Determinan Praktik Manajemen Laba Riil - Koerniawan Dwi Wibawa; Bambang Subroto; Wuryan Andyani (Jurnal Ekonomi Modernisasi, 2018)
The aim of this study was to examine the effect of the level financial statement disclosure on earnings management and audit quality in moderating this study. The sample of this study was from LQ45 companies, especially in manufacturing as many as 9 companies with an observation period of 5 years (2012-2016). This study provided empirical evidence that a negative influence between the level of disclosure of financial statements and real earnings management used production costs. But with the proxies of operational cash flow and discretionary costs produce provided a positive relationship. The results of the moderation regression test with production costs as proxy of earnings management provided that audit quality can strengthen the negative effect of the financial disclosure level on earnings management. Other results indicate that audit quality can strengthen the positive influence of the financial disclosure level on earnings management with a proxy for operational cash flows and discretionary costs. The Managerial implications of research was that auditors can examine other factors besides operational cash flow and discretionary costs in carrying out judgment on earnings management practices in the company.